Optimizing Public Perception: Understanding the Relationship Between Service Quality and STNK Service Satisfaction in Bandung's Public Service Mall - Elshiva Khoerunissa; Rizky Pramuditha; Atep Suhendar (Innovation Business Management and Accounting Journal, 2024)
The purpose of this research is to determine the extent of the influence of service quality on public satisfaction in the STNK tax service at the Public Service Mall in Bandung City. The population of this study is all vehicle taxpayers who pay STNK taxes. The sample used in this study consisted of 40 respondents. The data analysis method used is quantitative descriptive and simple regression analysis using SPSS version 25 as a tool. The descriptive survey method is a research method that samples from a population and uses questionnaires as a data collection tool. In this research, data and information are collected from respondents using questionnaires or surveys. The results of this study indicate that the influence of service quality on public satisfaction is positive. This means that service quality significantly affects public satisfaction. The findings underscore the crucial role of service quality in shaping public perception and satisfaction regarding STNK tax services. Policymakers and administrators should prioritize efforts to enhance service quality at the Public Service Mall in Bandung City to ensure positive outcomes for taxpayer satisfaction and overall public trust in governmental services.